Az MH-17 légi járat lelövésének nemzetközi jogi megítélése a nemzetközi polgári repülésről szóló Chicagói Egyezmény tükrében - Papp, Zoltán (Debreceni Jogi Műhely, 2019)
This paper addresses the downing of Malaysian Airlines flight MH-17 in 2014 from the perspective of the Chicago Convention on international civil aviation. Two issues are closely examined namely the applicability of Article 3bis on prohibiting the use of force by states against civil aircraft to the specific case and States’ obligation to close the airspace to civil aviation over conflict zones. If the assumption of the Joint Investigation Team is correct in that flight MH-17 was shot down from a territory held by separatist groups it will be a legally challenging task to prove the necessary link to Russia requried by international law to determine state responsability for the breach of Article 3bis. The fact that the International Court of Justice has never delivered a judgement on merits concerning aerial incident cases due to the lack of jurisdiction does not advance the prospect for a reassuring conclusion of the case concerning flight MH-17 from the perspective of international aviation law. The obligation to close the airspace by the state exercising sovereignty over the airspace over conflict zones is not spellt out explicitly in the Chicago Convention. States responsible for the airspace should however close their airspace if the airspace in question is not safe for civil aviation. The critical question remains whether the state responsible for the airspace has all the relevant information at its disposal when making the complex decision about closing the airspace. In case of a non-international armed conflict non-state actors are not obliged under the Chicago Convention to share aviation safety related information with the enemy state responsible for the airspace under international law over the conflict zone. It is hereby proposed that binding regulations should be adopted either in the field of international air law or humanitarian law to the effect that during an armed conflict non-state actors co-operate in information sharing for the sake of guaranteeing the safety of (international) air traffic.